Safety and Risk Factors of Needle Thoracentesis Decompression in Tension Pneumothorax in Patients over 75 Years Old - Yanhu Wang; Lei Wang; Cheng Chen; Yifan Que; Yinyi Li; Jiang Luo; Ming Yin; Miao Lv; Guogang Xu (Canadian Respiratory Journal)
Background. There are very few professional recommendations or guidelines on the needle thoracentesis decompression (NTD) for the tension pneumothorax in the elderly. This study aimed to investigate the safety and risk factors of tension pneumothorax NTD in patients over 75 years old based on CT evaluation of the chest wall thickness (CWT). Methods. The retrospective study was conducted among 136 in-patients over 75 years old. The CWT and closest depth to vital structure of the second intercostal space at the midclavicular line (second ICS-MCL) and the fifth intercostal space at the midaxillary line (fifth ICS-MAL) were compared as well as the expected failure rates and the incidence of severe complications of different needles. We also analyzed the influence of age, sex, presence or absence of chronic obstructive pulmonary disease (COPD), and body mass index (BMI) on CWT. Results. The CWT of the second ICS-MCL was smaller than the fifth ICS-MAL both on the left and the right side (P<0.05). The success rate associated with a 7 cm needle was significantly higher than a 5 cm needle (P<0.05), and the incidence of severe complications with a 7 cm needle was significantly less than an 8 cm needle (P<0.05). The CWT of the second ICS-MCL was significantly correlated with age, sex, presence or absence of COPD, and BMI (P<0.05), whereas the CWT of the fifth ICS-MAL was significantly correlated with sex and BMI (P<0.05). Conclusion. The second ICS-MCL was recommended as the primary thoracentesis site and a 7 cm needle was advised as preferred needle length for the older patients. Factors such as age, sex, presence or absence of COPD, and BMI should be considered when choosing the appropriate needle length.